Legal Protection for the Image of Children and Women Related to Body Shaming in the Community - Limbong, Hotma Ringan; Istiadah, Istiadah (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2021)
Body Shaming (insulting body image) is a form of physical criticism of oneself or others in a way that is considered trivial but has negative consequences for both oneself and others. Currently, bullying is becoming a concern for international institutions, one of which is the Plan International Center For Research On Women (ICRW) in 5 Asian countries, namely Vietnam (79%), Cambodia (73%), Nepal (79%), Pakistan (43%), and Indonesia (84%). The bullying behavior carried out is in the form of physical bullying, verbal bullying, rational bullying and cyberbullying. The method used is descriptive-analytical with the aim of knowing law enforcement against children and women related to body shaming in society. In conclusion, protection against body shaming among children and women really requires attention from government officials regarding more effective protection and law enforcement, and increasing awareness among the public.